Prevalence of genetically defined familial hypercholesterolemia and the impact on acute myocardial infarction in Taiwanese population: A hospital-based study - Chen, Yen-Ju; Chen, I-Chieh; Chen, Yi-Ming; Hsiao, Tzu-Hung; Wei, Chia-Yi; Chuang, Han-Ni; Lin, Wei-Wen; Lin, Ching-Heng (Frontiers in Cardiovascular Medicine, 2022)
Background Familial hypercholesterolemia (FH) is a common genetic disorder with markedly increased risk of coronary artery diseases (CAD), especially acute myocardial infarction (AMI). However, genetic tests for FH are not always necessary in the current diagnostic criteria of FH, which might lead to underestimation of the prevalence of FH and a lack of awareness of FH-associated CAD and AMI. We aimed to explore the prevalence of genetically defined FH in the hospital-based population and to determine the impact of FH risk variants on CAD and AMI. Methods The study participants were recruited between June 24, 2019 and May 12, 2021, at a medical center in Taiwan, in cooperation with the Taiwan Precision Medicine Initiative (TPMI) project. The prevalence of FH was calculated and the effects of FH pathogenic variants on CAD and AMI were analyzed by logistic regression models and shown as ORs and 95% CI. Results The prevalence of genetically defined FH was 1.13% in the hospital-based population in Taiwan. Highest LDL and total cholesterol levels were observed in patients with LDLR rs28942084 (LDL 219.4±55.2; total cholesterol 295.8±55.4). There was an approximately 4-fold increased risk of hyperlipidemia in subjects with the LDLR rs769446356 polymorphism (OR, 4.42; 95% CI, 1.92-10.19) and AMI in individuals with the LDLR rs730882109 polymorphism (OR, 3.79; 95% CI, 2.26-6.35), and a 2-fold increased risk of CAD in those with the LDLR rs749038326 polymorphism (OR, 2.14; 95% CI, 1.31-3.50), compared with the groups without pathogenic variants of FH. Conclusions The prevalence of genetically defined FH was 1.13% in the hospital-based population in Taiwan, which was higher than the rate observed in individuals with clinically defined FH. The risk of CAD and AMI was increased to varying degrees in subjects with different FH risk alleles. Close monitoring and risk stratification strategy are essential in high-risk patients with FH risk alleles to facilitate early detection and treatments.